Asymmetric Supercapacitors: Optical and Thermal Effects When Active Carbon Electrodes Are Embedded with Nano-Scale Semiconductor Dots - Haim Grebel (C, 2021)
Optical and thermal effects in asymmetric supercapacitors, whose active-carbon (AC) electrodes were embedded with nano-Si (n-Si) quantum dots (QD), are reported. We describe two structures: (1) p-n-like, obtained by using a polyethylimine (PEI) binder for the “n” electrode and a polyvinylpyrrolidone (PVP) binder for the “p” electrode; (2) a single component binder—poly(methyl methacrylate) (PMMA). In general, AC appears black to the naked eye and one may assume that it indiscriminately absorbs all light spectra. However, on top of a flat lossy spectrum, AC (from two manufacturers) exhibited two distinct absorption bands: one in the blue (~400 nm) and the other one in the near IR (~840 nm). The n-Si material accentuated the absorption in the blue and bleached the IR absorption. Both bands contributed to capacitance increase: (a) when using aqueous solution and a PMMA binder, the optical-related increased capacitance was 20% for low n-Si concentration and more than 100% for a high-concentration dose; (b) when using ion liquid (IL) electrolyte, the large, thermal capacitance increase (of ca. 40%) was comparable to the optical effect (of ca. 42%) and hence was assigned as an optically induced thermal effect. The experimental data point to an optically induced capacitance increase even in the absence of the n-Si dots. Overall, the experimental data suggest intriguing possibilities for optically controlled supercapacitors.